AML: high serum ferritin at initial diagnosis has a negative impact on long-term survival. Issue 1 (2nd January 2019) - Ihlow, Jana; Gross, Sophia; Sick, Annabel; Schneider, Tanja; Flörcken, Anne; Burmeister, Thomas; Türkmen, Seval; Arnold, Renate; Dörken, Bernd; Westermann, Jörg
Abstract: Increased serum ferritin (SF) is common in hematologic malignancies; however, its prognostic role in acute myeloid leukemia (AML) is not clearly established. We examined the impact of baseline SF on long-term survival in 137 intensively treated AML patients. Patients and baseline characteristics were retrieved from an AML database at Charité University Medical Center Berlin, Campus Virchow Clinic. After c-reactive protein (CRP)-based adjustment for inflammation, patients were grouped according to their baseline SF level. Survival analysis was performed accordingly. A significant decline in overall survival and relapse-free survival was observed in patients with high SF as compared to those with low SF. Furthermore, elevated baseline SF remained an independent poor prognostic factor within the multivariate analysis and was associated with a significant higher risk of relapse and non-relapse mortality (NRM). In conclusion, our data show that elevated baseline SF has a negative impact on long-term survival in intensively treated AML patients.